Regeneration of Complex Capital Goods Contributions to the Final Symposium of the Collaborative Research Center 871 - Seume, Joerg R.; Denkena, Berend; Gilge, Philipp; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2025)
This open access book compiles the groundbreaking research conducted by the Collaborative Research Center (CRC) 871, centered around the "Regeneration of Complex Capital Goods." This comprehensive work unveils an array of innovative methods developed through CRC 871, designed to revitalize and enhance the functional attributes of these critical assets. From non-destructive characterization of heavily stressed turbine components to the dynamic behavior of regenerated structural elements, each chapter offers a meticulous exploration of diverse facets in the field. The book also addresses the crucial consideration of variability in repair processes and material properties, as well as the comprehensive control of regeneration processes. With insights into simulation-based process design, fast measurement techniques, and resilience-based decision criteria, this volume provides a comprehensive view of the cutting-edge approaches employed. Moreover, readers will find a detailed process chain for condition-based regeneration, offering a practical framework for implementation. Finally, the book sheds light on the importance of targeted public relations in disseminating the invaluable research carried out by Collaborative Research Center 871. This extensive compilation not only showcases the scientific rigor behind maintaining complex capital goods but also demonstrates the collaborative efforts that brought together experts from various fields to push the boundaries of regeneration technology.
Introduction -- Inspection and Condition Assessment (Project Area A) -- Non-Destructive Characterization of Coating and Material Conditions of Heavily Stressed Turbine Components -- Multiscale Measurement of Blade Geometries with Robot-Supported, Laser-Positioned Multi-Sensor-Techniques -- Exhaust Jet Analysis -- Adaptable and Component-Protecting Disassembly in the Regeneration Path -- Impact of Mixing on the Signature of Combustor Defects -- Interaction between Production Processes and the Product$1 (Bs Functional Characteristics (Project Area B) -- Near Net Shape Turbine Blade Repair Using a Joining and Coating Hybrid Process107 B2 Dexterous Regeneration Cell -- Influence of Complex Surface Structures on the Aerodynamic Loss Behaviour of Blades -- Dynamical Behaviour and Strength of Structural Elements with Regeneration In- duced Imperfections and Residual Stresses -- Single Crystalline Laser Welding -- Regeneration and Surface Hardening of Titanium Components Using the Example of Titanium Alloy Ti6Al4V -- Consideration of Variability in the Repair Processes and in Material Pro- perties (Project Area C) -- Simulation-Based Process Design of Recontouring Technologies -- Fast Measurement of Complex Geometries using Inverse Fringe Projection -- Regeneration-induced Variances of Aeroelastic Properties of Turbine Blades -- Prediction of Fatigue Lifetime Using aWavelet Transformation Induced Multi-time Scaling Method and XFEM -- Influence of Regeneration-induced Mistuning on the Aeroelasticity of Multistage Axial Compressors -- Comprehensive Control of the Regeneration Processes (Project Area D) -- Modeling, Configuration and Assessment of Regeneration Supply Chains -- Selection of Efficient Regeneration Modes for the Regeneration of Complex Capital Goods -- Resilience-based Decision Criteria for Optimal Regeneration -- Interaction of Combined Module Variances and Influence on the OverallSystem Behaviour -- Process Chain for Condition-based Regeneration -- Target-Group Based Public Relations for the Collaborative Research Center.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Mechanical engineering; Mechanical Engineering